2012
DOI: 10.3233/s12349-012-0097-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary strategy for prevention and management of dyslipidemia: international guidelines

Abstract: Primary prevention of cardiovascular disease should begin with a detailed metabolic study of our patients who must follow a nutritional therapy. Recently, new guidelines ESC/EAS 2011 on the treatment of dyslipidemia have been drawn up, according to which it is possible to arrive at desirable values of cholesterol and triglycerides with a synergy between drug treatment and adequate diet therapy. At this time, Mediterranean diet has been undergoing a radical transformation: there is hyperalimentation of the Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Phosphorylated ACLY plays a role in regulating inflammation and repairing DNA damage in macrophages, cancer cells and T cells, because it regulates the nuclear acetylation of substrates at the level of these cells. Finally, it has been observed that ACLY is highly expressed in some pathological conditions, such as in the fasting of obese patients with high insulin resistance [11]. This enzyme intervenes in lipid metabolism by catalyzing the following reaction: citrate + ATP + CoA → oxaloacetate + acetyl-CoA + ADP + Pi (Fig.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Phosphorylated ACLY plays a role in regulating inflammation and repairing DNA damage in macrophages, cancer cells and T cells, because it regulates the nuclear acetylation of substrates at the level of these cells. Finally, it has been observed that ACLY is highly expressed in some pathological conditions, such as in the fasting of obese patients with high insulin resistance [11]. This enzyme intervenes in lipid metabolism by catalyzing the following reaction: citrate + ATP + CoA → oxaloacetate + acetyl-CoA + ADP + Pi (Fig.…”
Section: Pharmacodynamicsmentioning
confidence: 99%